2022
DOI: 10.17079/jkgn.2022.24.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Depression in Older Adults According to Family Structure (Older Adults Living with Adult Children, a Spouse, or Alone): Data from the 2020 National Older Koreans Data

Abstract: Purpose: This descriptive research study aimed to identify the factors that influence depression according to household type (older adults who live with a spouse, adult children, or alone).Methods: A total of 9,790 older adults were selected and analyzed using the 2020 National Older Koreans data. A Rao-Scott x2 test was conducted to evaluate the differences in the individual, health-behavior, and mental-health factors according to family structure. A complex samples logistic regression was used to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…It was found that the higher the risk of depression, especially for women, the smaller the number of household members, the lower the satisfaction level of leisure life, the lower the family support and social support, and the lower the level of subjective health awareness. These results were aligned with the same context as previous studies 18 , 35 37 . The level of depression according to income level can also be examined.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was found that the higher the risk of depression, especially for women, the smaller the number of household members, the lower the satisfaction level of leisure life, the lower the family support and social support, and the lower the level of subjective health awareness. These results were aligned with the same context as previous studies 18 , 35 37 . The level of depression according to income level can also be examined.…”
Section: Discussionsupporting
confidence: 91%
“…Another study reported that life satisfaction and subjective health awareness have the most significant influence 34 . Depression in the elderly has been shown to have a significant psychological impact, and decision trees are reported to be a highly effective method 35 , 36 . In order to prevent and manage depression in the elderly, it is necessary to recognize the need for policy support considering psychological factors (subjective health awareness, leisure life satisfaction, family support, and social support).…”
Section: Discussionmentioning
confidence: 99%
“…Depression increased over time among older individuals living alone according to the study. This finding aligns with previous research on depression in individuals living alone [19,27,28,34], as well as the literature on depression changes in older adults [36][37][38][39]. The results of these studies highlight the need for social attention and intervention for depression among older individuals living alone.…”
Section: Discussionsupporting
confidence: 89%
“…Another study on social isolation suggested that living alone can easily result in social isolation and that may have a detrimental effect on cognitive function [33]. In the case of South Korea, research indicates that older individuals living alone suffer from a greater degree of depression than older individuals living with their children or older couples [34]. There has been a steady increase in the percentage of older people living alone in South Korea, reaching 34.9% in 2022, and this percentage is projected to continue to rise in the future [35].…”
Section: Introductionmentioning
confidence: 99%